Viral infection disrupts intestinal homeostasis via Sting-dependent NF-?B signaling in Drosophila. - Nigg, J.C.; Castelló-Sanjuán, M.; Blanc, H.; Frangeul, L.; Mongelli, V.; Godron, X.; Bardin, A.J.; Saleh, M.C. (Current Biology, 2024)
Host-microbe interactions influence intestinal stem cell (ISC) activity to modulate epithelial turnover and composition. Here, we investigated the functional impacts of viral infection on intestinal homeostasis and the mechanisms by which viral infection alters ISC activity. We report that Drosophila A virus (DAV) infection disrupts intestinal homeostasis in Drosophila by inducing sustained ISC proliferation, resulting in intestinal dysplasia, loss of gut barrier function, and reduced lifespan. We found that additional viruses common in laboratory-reared Drosophila also promote ISC proliferation. The mechanism of DAV-induced ISC proliferation involves progenitor-autonomous epidermal growth factor receptor (EGFR) signaling, c-Jun N-terminal kinase (JNK) activity in enterocytes, and requires Sting-dependent nuclear factor ?B (NF-?B) (Relish) activity. We further demonstrate that activating Sting-Relish signaling is sufficient to induce ISC proliferation, promote intestinal dysplasia, and reduce lifespan in the absence of infection. Our results reveal that viral infection can significantly disrupt intestinal physiology, highlight a novel role for Sting-Relish signaling, and support a role for viral infection in aging.